KUALITAS PELAYANAN PEMBUATAN KARTU KELUARGA (KK) PADA KANTOR KECAMATAN - Nurmas Hasanah Tanjung; Euis Salbiah; Afmi Apriliani (LPPM Universitas Djuanda Bogor, 2022)
This study aims to determine the Quality of Service for Making Family Cards (KK), service quality is a comparison between consumer expectations and service performance, while the Family Card is one of the civil registration documents that must be owned by every head of the family, but complaints are still found in the manufacture service. family card at the Ciawi District Office, Bogor Regency. In this study using a descriptive method with a quantitative approach. The population in this study were people who received the service of making Family Cards at the Ciawi District office with a sample of 78 respondents. namely the people found who were doing the service of making Family Cards (KK) at the Ciawi District Office. The results show that in general the service for making Family Cards in Ciawi District has been going well, but there are still several dimensions that are still below the average variable value, namely the empathy dimension with an average value of 4.17, the reliability dimension. the average score is 4.16, and the dimension of assurance (assurance) with an average value of 4.17.